THE EFFECT OF DEPOT MEDROXYPROGESTERONE ACETATE ADMINISTRATION ON THE LEVELS OF FOLLICLE-STIMULATING HORMONE, PROGESTERONE, ESTRADIOL, AND CALCIUM - Siregar, Nurelilasari; Rita, Rauza Sukma; Yusrawati, Yusrawati (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The purpose of this research is to determine the effect of depot medroxyprogesterone acetate (DMPA) on the levels of follicle-stimulating hormone (FSH), progesterone, estradiol, and calcium. Methods: This was a cross-sectional study, this study was conducted in the region of Lubuk Buaya Health Care and Andalas Health Care on September– November 2017. Examination of FSH, progesterone, and estradiol levels was performed in the Laboratory Biomedicine, Faculty of Medicine, Andalas University by ELISA method, and the examination of calcium level was performed in Laboratory Biochemistry, Faculty of Medicine, Andalas University by calcium Arsenazo method. Then, the data were analyzed by Kolmogorov–Smirnov and independent t-test. Results: This study showed that there was a significant difference of FSH, progesterone, estradiol, and calcium levels on KB DMPA acceptors and non-acceptors with p<0.05. Conclusion: The use of contraception DMPA has the effect on the levels of FSH, progesterone, estradiol, and calcium in the blood.